A MOF-CGC material and its preparation method and application

By converting metal organic frame crystals into glass under a protective atmosphere and reacting with organic ligands, the problem of high temperatures required for the preparation of existing MOF-CGC materials is solved, and the preparation of MOF-CGC materials at lower temperatures is realized, which broadens the material selection range and reduces the preparation cost.

CN119505275BActive Publication Date: 2025-04-29NINGBO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510083838.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The preparation of existing MOF-CGC materials requires high temperature treatment, which limits the type of MOF crystal materials and the development of MOF-CGC materials. Especially metal frame materials with poor thermal stability cannot be prepared by blending and melting method.

Method used

The metal organic frame crystal is melted by heat treatment under a protective atmosphere, and then quickly cooled to form a glass, which is then mixed with the organic ligand and heated to induce sublimation of the organic ligand, reacting with the metal organic frame glass to form a MOF-CGC material. This method can realize the preparation of MOF-CGC materials at lower temperatures.

Benefits of technology

The selection range of metal organic frames in MOF-CGC materials has been broadened, the preparation temperature is reduced, energy consumption is reduced, and the preparation cost-effectiveness and controllability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505275B_ABST
    Figure CN119505275B_ABST
Patent Text Reader

Abstract

The present invention provides a MOF-CGC material and a preparation method and application thereof, and relates to the field of metal organic framework materials. The preparation method of the MOF-CGC material provided by the present invention comprises the following steps: S1: in a protective gas atmosphere, heat-treating a metal organic framework crystal so that the crystal reaches a molten state, and then rapidly cooling to obtain a metal organic framework glass; S2: mixing the metal organic framework glass obtained in step S1 with an organic ligand and placing it in a reactor, heating and treating to induce sublimation of the organic ligand, so that the organic ligand vapor reacts with the metal organic framework glass, and obtaining a MOF-CGC material after the reaction is completed. The present invention can prepare a MOF-CGC material by a two-step method, and has the advantages of low preparation cost, wide application range, simple operation, and high universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of metal organic framework materials, and in particular, relates to a MOF-CGC material and a preparation method and application thereof. Background Art

[0002] Metal-organic framework (MOF) glass is an important derivative of MOF materials, which is prepared by heat-treating fusible MOF crystals. Based on the phase change process of crystal-liquid-glass, MOF glass materials exhibit unique processing properties and can be made into powders, blocks, coatings, self-supporting films, etc. However, the number of MOF glasses and fusible MOFs is relatively small, with 20-30 types reported so far, and many types are highly similar in structure. This leads to limitations in the regulation of the physical and chemical structure of MOF glass materials, making it difficult to fully meet the application needs in gas separation, catalysis, batteries and other fields.

[0003] Metal-organic framework crystal and glass composite (MOF-CGC) materials are composite materials that integrate MOF glass and MOF crystals. They are generally prepared by mixing non-melting MOF crystals and meltable MOF crystal spheroidal graphite, and then treating them at high temperature (above 400°C). This method is based on the phase change process of meltable MOF to achieve homogeneous mixing and finally form MOF-CGC materials. Since MOF crystals and MOF glass have similar structures and good interface compatibility, the interface defect problem of traditional MOF crystals and polymer composites has been improved. However, the preparation of MOF-CGC materials still needs to undergo a high-temperature treatment process, which requires that the adapted MOF crystal materials need to have high thermal stability and oxidation-resistant chemical groups. Metal framework materials with poor thermal stability such as ZIF-8 and Zn(Trz)2 cannot be used to prepare MOF-CGC materials by the blending and melting method, which limits the further development of MOF-CGC materials. Summary of the invention

[0004] The purpose of the present invention is to develop a preparation method for MOF-CGC material at a relatively low temperature.

[0005] To achieve the above object, the first aspect of the present invention provides a method for preparing a MOF-CGC material, which specifically comprises the following steps:

[0006] S1: Under a protective gas atmosphere, the metal organic framework crystal is heated to a molten state, and then rapidly cooled to obtain the metal organic framework glass;

[0007] S2: The metal organic framework glass obtained in step S1 and the organic ligand are mixed and placed in a reactor, and heated to induce sublimation of the organic ligand, so that the organic ligand vapor reacts with the metal organic framework glass, and after the reaction is completed, a MOF-CGC material is obtained.

[0008] Different from the existing preparation method of MOF-CGC materials, the preparation method provided by the present invention first converts the MOF crystal into MOF glass, and then the MOF-CGC material can be prepared at a relatively low temperature.

[0009] Preferably, the metal organic framework crystal is selected from [Zn(HPO4)(H2PO4)2](ImH2)2, [Zn3(H2PO4)6(H2O)3](HbIm), [Zn3(H2PO4)6(H2O)3](HmbIm), [Zn3(H2PO4)6(H2O)3](BTA), [Zn(H2PO4)2(HPO4)](H2dmbIm)2, Zn(HTr)2(H2PO4)2, ZIF-4, Zn(Im)2(GIS), ZIF-62(Zn), ZIF-62(Co), ZIF-76, ZIF-76-mblm, TIF-4, Zn(Im)2(GIS), ZIF-62(Zn), ZIF-62(Co), ZIF-76, ZIF-76-mblm, TIF-4, Zn(Im)2(GIS), Zn(H2PO4)6(H2O)3](HbIm), Zn3(H2PO4)6(H2O)3](HmbIm), Zn3(H2PO4)6(H2O)3](BTA), Zn(H2PO4)2(HPO4)](H2dmbIm)2, Zn(HTr)2(H2PO4)2 1.95 (bIm) 0.025 (ClbIm) 0.025 、Co 0.2 Zn 0.8 (Im) 1.95 (bIm) 0.025 (ClbIm) 0.025 , any one or more of ZIF-UC-2, ZIF-UC-3, ZIF-UC-4, and ZIF-UC-5.

[0010] Preferably, in step S1, the heating temperature is 50-800°C.

[0011] Preferably, in step S1, the cooling rate is 1-50°C / min.

[0012] In step S1 of the present invention, the MOF materials such as phosphate-imidazole and zeolite imidazole can be used to vitrify the MOF crystals after reaching a molten state under a protective gas atmosphere by rapid cooling, which has the advantage of convenient and simple operation. At the same time, the technical solution provided by the present invention does not impose any restrictions on the morphology of the metal organic framework glass obtained in step S1, and the aggregation form of the metal organic framework glass material can be selected from any one of powder, block, film, and base coating.

[0013] Preferably, in step S2, the organic ligand is selected from any one or more of imidazole, 2-methylimidazole, 2-aminoimidazole, benzimidazole, 2-chlorobenzimidazole, 5-chlorobenzimidazole, 5-methylbenzimidazole, 5,6-dimethylbenzimidazole, pyridine, p-aminopyridine, 2-aminopyridine, 3-aminopyridine, 1,2,4-triazole, and 1,2,3-triazole.

[0014] Preferably, in step S2, the temperature of the heating treatment is 50-400°C.

[0015] More preferably, in step S2, the temperature of the heating treatment is 100-200°C.

[0016] Existing MOF-CGC materials are prepared by blending and melting, and a heating temperature higher than 400°C is required during the preparation process, which limits the types of MOF crystal materials and has great limitations. The preparation method provided by the present invention can achieve the preparation of MOF-CGC materials at a relatively low temperature, and has a wider applicability.

[0017] Preferably, in step S2, the reaction time is 1 min to 7 d.

[0018] In step S2 of the present invention, imidazole organic ligands, benzimidazole organic ligands, pyridine organic ligands, and triazole organic ligands can be sublimated into organic ligand vapor at a relatively low temperature, and the formed organic ligand vapor can directly react with metal organic framework glass to generate MOF-CGC material. The technical solution provided by the present invention does not impose any restrictions on the morphology of the MOF-CGC material obtained in step S2, and the aggregation form of the MOF-CGC material can be selected from any one of powder, block, film, and base coating.

[0019] Preferably, in step S1, components of the protective gas atmosphere are selected from any one or more of nitrogen, helium, argon and air.

[0020] The second aspect of the present invention provides a MOF-CGC material, which is prepared by the preparation method described in the first aspect, and the MOF-CGC material includes a metal organic framework crystal phase and a metal organic framework glass phase in any ratio.

[0021] The third aspect of the present invention provides an application of a MOF-CGC material, wherein the MOF-CGC material described in the second aspect is used for gas adsorption.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention can realize the preparation of MOF-CGC materials in two steps, wherein the formation of metal organic framework crystals is based on the induced transformation of organic ligands, and the reaction temperature for forming MOF-CGC materials can be reduced to below 200°C, which broadens the selection range of metal organic frameworks in MOF-CGC materials and makes the types of MOF-CGC materials more diversified. At the same time, lower reaction temperature also means less energy consumption. The preparation method provided by the present invention also has the advantage of lower preparation cost.

[0024] 2. The preparation method of the MOF-CGC material provided by the present invention also has excellent controllability. In the preparation method provided by the present invention, the composition, proportion, porosity and topological structure of the metal organic framework crystal phase and the metal organic framework glass phase of the product MOF-CGC material can be changed accordingly by simply controlling the type of metal organic framework crystal or metal organic framework glass, the type of organic ligand, the organic ligand vapor reaction time and the reaction temperature. The operation is simple and controllable.

[0025] 3. The MOF-CGC material provided by the present invention also has excellent universality. Since the final reaction is the reaction of organic ligand vapor with metal-organic framework glass, the aggregation form of the metal-organic framework glass used for the reaction actually includes but is not limited to powder, block, film, and substrate coating. In addition, during the preparation process, the preparation method provided by the present invention can control the location where the reaction occurs and the degree of the reaction through the template, which can be used for the structural optimization of MOF-CGC materials and the patterned design of the substrate surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the X-ray diffraction result of ZIF-62-Mim prepared in Example 1 of the specific implementation mode of the present invention;

[0027] Figure 2 This is a scanning electron microscope photograph of ZIF-62-Mim prepared in Example 1 of the specific embodiment of the present invention;

[0028] Figure 3 This is the BET test result of ZIF-62-Mim prepared in Example 1 of the specific embodiment of the present invention;

[0029] Figure 4 The DSC test results of ZIF-62-Mim prepared in Example 1 of the specific embodiment of the present invention;

[0030] Figure 5 This is a scanning electron microscope photo of ZIF-62-Bim-Cl prepared in Example 2 of the specific embodiment of the present invention;

[0031] Figure 6 This is an electron microscope photograph of the ZIF-62-Trz metal organic framework crystal and glass composite coating prepared in Example 3 of the specific embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0033] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0034] The specific embodiment of the present invention provides a method for preparing MOF-CGC material at a relatively low temperature, which specifically comprises the following steps:

[0035] S1: Under a protective gas atmosphere, the metal organic framework crystal is heated to a molten state, and then rapidly cooled to obtain the metal organic framework glass;

[0036] S2: The metal organic framework glass obtained in step S1 and the organic ligand are mixed and placed in a reactor, and heated to induce sublimation of the organic ligand, so that the organic ligand vapor reacts with the metal organic framework glass, and after the reaction is completed, a MOF-CGC material is obtained.

[0037] Part of the metal organic framework crystal material can be converted into metal organic framework glass in a molten state. Therefore, in the above embodiment, the purpose of step S1 is to obtain metal organic framework glass.

[0038] In a specific embodiment, the material of the metal organic framework crystal is selected from any one or more of phosphoric acid-azole series metal organic framework crystals, zeolite imidazole series metal organic framework crystals, and halogenated imidazole series metal organic framework crystals.

[0039] In a specific embodiment, the phosphoric acid-azole series metal organic framework crystals are selected from any one or more of [Zn(HPO4)(H2PO4)2](ImH2)2, [Zn3(H2PO4)6(H2O)3] (HbIm), [Zn3(H2PO4)6(H2O)3](HmbIm), [Zn3(H2PO4)6(H2O)3](BTA), [Zn(H2PO4)2(HPO4)](H2dmbIm)2, Zn(HTr)2(H2PO4)2, the zeolite imidazole series metal organic framework crystals are selected from any one or more of ZIF-4, Zn(Im)2(GIS), ZIF-62(Zn), ZIF-62(Co), ZIF-76, ZIF-76-mblm, TIF-4, and the halogenated imidazole series metal organic framework crystals are selected from Zn(Im) 1.95 (bIm) 0.025 (ClbIm) 0.025 、Co 0.2 Zn 0.8 (Im) 1.95 (bIm) 0.025 (ClbIm) 0.025 , any one or more of ZIF-UC-2, ZIF-UC-3, ZIF-UC-4, and ZIF-UC-5.

[0040] More specifically, the metal organic framework glass is selected from ZIF-62, TIF-4, Zn(Im) 1.95 (bIm) 0.025 (ClbIm) 0.025 , [Zn(HPO4)(H2PO4)2](ImH2)2.

[0041] In step S1 of the specific embodiment, the heating temperature is 50-800°C.

[0042] In step S1 of the specific embodiment, the heating rate is 1-50° C. / min.

[0043] In step S1 of the specific embodiment, the cooling rate is 1-50° C. / min.

[0044] In step S1 of the specific embodiment, the components of the protective gas atmosphere are selected from any one or more of nitrogen, helium, argon and air.

[0045] In step S2 of a specific embodiment, the organic ligand is selected from any one or more of imidazole, 2-methylimidazole, 2-aminoimidazole, benzimidazole, 2-chlorobenzimidazole, 5-chlorobenzimidazole, 5-methylbenzimidazole, 5,6-dimethylbenzimidazole, pyridine, p-aminopyridine, 2-aminopyridine, 3-aminopyridine, 1,2,4-triazole, and 1,2,3-triazole.

[0046] In step S2 of a specific embodiment, the organic ligand is selected from any one of imidazole, 2-methylimidazole, benzimidazole, 5-chlorobenzimidazole, and 1,2,4-triazole.

[0047] In step S2 of the specific embodiment, the temperature of the heating treatment is 50-400°C.

[0048] More specifically, the heating temperature is 100 to 200°C.

[0049] In step S2 of the specific embodiment, the reaction time is 1 min to 7 d.

[0050] The preparation method provided in the above embodiment can realize the preparation of MOF-CGC material in two steps, and the reaction temperature for finally forming MOF-CGC material can be compressed to below 200°C, which broadens the selection range of metal organic frameworks in MOF-CGC materials and diversifies the types of MOF-CGC materials. At the same time, by simply controlling the type of metal organic framework crystal or metal organic framework glass, the type of organic ligand, the reaction time of organic ligand vapor, and the reaction temperature, the composition, proportion, porosity and topological structure of the metal organic framework crystal phase and the metal organic framework glass phase of the product MOF-CGC material can be changed accordingly. The operation is simple and controllable. In addition, the above preparation method has excellent universality and is suitable for powders, blocks, membranes, coatings on substrates, etc., and the location and degree of conversion of the reaction can be regulated by a template, which can be used for gas separation material structure optimization and substrate surface patterning design.

[0051] The technical solution of the present invention is further described below through specific embodiments.

[0052] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, the terms with conventionally understood meanings are defined herein for the purpose of illustrating or facilitating reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available reagents and instruments is carried out in accordance with the schemes and parameters given by the manufacturer.

[0053] Example 1

[0054] Preparation of ZIF-62-Mim

[0055] S1: Place ZIF-62 crystal powder in a tubular furnace, and heat it from room temperature to 450°C at a heating rate of 10°C / min under argon protection. After staying at 450°C for 5 minutes, stop heating immediately and cool naturally to room temperature to obtain ZIF-62 glass material.

[0056] S2: Place ZIF-62 glass material and organic ligand 2-methylimidazole (Mim) in a reactor, raise the temperature to 120°C, sublimate Mim, and react Mim vapor with the metal organic framework glass for 24 hours to reconstruct the structure to form the MOF-CGC material ZIF-62-Mim.

[0057] The above ZIF-62-Mim was subjected to X-ray diffraction, and the XRD results are as follows: Figure 1 As shown, ZIF-62-Mim shows Bragg characteristic peaks consistent with those of ZIF-8, indicating that after ligand transformation, the original ligands of ZIF-62 glass and Mim undergo a replacement process, thereby forming a metal-organic framework crystal and glass composite structure.

[0058] The above ZIF-62-Mim was observed by scanning electron microscope, as shown in the following picture: Figure 2 As shown by Figure 2 It can be seen that under the SEM electron microscope, the ZIF-62-Mim material as a whole presents a blocky morphology with obvious spherical protrusions on the surface, where the protrusions are the metal-organic framework crystal phase in ZIF-62-Mim, and the main body is the metal-organic framework glass phase of ZIF-62-Mim.

[0059] The porosity of the above ZIF-62-Mim was tested by BET, and the results are as follows: Figure 3 As shown in the figure, the ZIF-62 glass phase has small pores and basically does not adsorb nitrogen at 77 K. However, the adsorption capacity of nitrogen by ZIF-62-Mim reaches 109.6 cm 3 / g, indicating that ZIF-62-Mim integrates the pore structures of crystals and glass, which further illustrates that metal-organic framework crystals and metal-organic framework glass composites (MOF-CGC) have porosity and pore structure superior to those of metal-organic framework glass.

[0060] The glass transition temperature of the above ZIF-62-Mim was tested by DSC, and the results are as follows: Figure 4 As shown by Figure 4 It can be seen that along with the heating process, an obvious endothermic process was observed at 315 °C, which also shows that ZIF-62-Mim still retains the glass phase and has not completely transformed into a crystal.

[0061] Comparative Example 1

[0062] Preparation of ZIF-62 and ZIF-8 composites by melt blending

[0063] ZIF-8 crystals and ZIF-62 crystals were preliminarily mixed in a molar ratio of 1:1, and then the powders were ball milled at a speed of 300 rpm for 1 h to achieve uniform mixing of the two. The powders were then placed in a tube furnace and heated from room temperature to 450°C at a heating rate of 10°C / min under argon protection. After staying at 450°C for 5 minutes, the heating was immediately stopped and naturally cooled to room temperature to obtain ZIF-62 and ZIF-8 metal organic framework glass composites. Metal organic framework crystals and glass composites (MOF-CGC) with high porosity were not prepared.

[0064] It can be seen from Example 1 and Comparative Example 1 that the preparation method of the MOF-CGC material provided by the present invention broadens the selection range of the metal organic framework in the MOF-CGC material, and the final reaction temperature is also lower than that of the prior art, which has the advantages of lower cost and wider application range.

[0065] Example 2

[0066] Preparation of ZIF-62-Bim-Cl

[0067] S1: Place ZIF-62 crystal powder in a mold, and heat it from room temperature to 450°C at a heating rate of 10°C / min under argon protection. After staying at 450°C for 5 minutes, stop heating immediately and cool naturally to room temperature to obtain ZIF-62 glass material.

[0068] S2: Place ZIF-62 glass material and 5-chlorobenzimidazole (Bim-Cl) in a reactor, raise the temperature to 200°C, sublimate Bim-Cl, and react Bim-Cl vapor with the metal organic framework glass for 24 hours to reconstruct the structure to form the MOF-CGC material ZIF-62-Bim-Cl.

[0069] The above ZIF-62-Bim-Cl was observed by scanning electron microscope, and the SEM photos are as follows: Figure 5 As shown, the structure of ZIF-62-Bim-Cl is 1 cm 2 The square block is composed of Figure 5 It can be seen that the surface of ZIF-62-Bim-Cl presents a scaly lamellar structure, which indicates that the original ligands of ZIF-62 glass and Bim-Cl undergo a replacement process, thereby forming a metal-organic framework crystal and glass composite structure.

[0070] Example 3

[0071] Preparation of ZIF-62-Trz

[0072] S1: ZIF-62 crystal powder was deposited on a silicate glass substrate, placed in a tubular furnace, and heated from room temperature to 450°C at a heating rate of 10°C / min under argon protection. After staying at 450°C for 5 minutes, the heating was immediately stopped and naturally cooled to room temperature to obtain a silicate glass sheet with a ZIF-62 glass coating, recorded as M1.

[0073] S2: M1 and 1,2,4-triazole (Trz) were placed in a reactor, the temperature was raised to 80°C, Trz sublimated, half of M1 was covered with aluminum oxide foil, Trz vapor reacted with the other half of M1 for 6 h, the structure was reconstructed to form ZIF-62-Trz, and ZIF-62-Trz metal organic framework crystals and glass composite coatings were obtained.

[0074] The ZIF-62-Trz metal organic framework crystal and glass composite coating were observed by scanning electron microscopy. Figure 6 As shown by Figure 6 It can be seen that the original ligands and Trz of the ZIF-62 glass in contact with the ligand vapor undergo a replacement process to form a crystalline phase. The part covered by the aluminum oxide foil retains the original morphology of the ZIF-62 glass.

[0075] Example 4

[0076] Preparation of ZIF-62-Bim

[0077] S1: Place the ZIF-62 crystal powder in a tubular furnace, and heat it from room temperature to 450°C at a heating rate of 10°C / min under argon protection. After staying at 450°C for 5 minutes, stop heating immediately and cool naturally to room temperature to obtain ZIF-62 glass powder.

[0078] S2: Place ZIF-62 glass powder and benzimidazole (Bim) in a reactor, raise the temperature to 200°C, sublimate Bim, and react Bim vapor with the metal organic framework glass for 24 hours to reconstruct the structure to form the MOF-CGC material ZIF-62-Bim.

[0079] Example 5

[0080] Preparation of ZIF-62-Im

[0081] S1: Place the ZIF-62 crystal powder in a tubular furnace, and heat it from room temperature to 450°C at a heating rate of 10°C / min under argon protection. After staying at 450°C for 5 minutes, stop heating immediately and cool naturally to room temperature to obtain ZIF-62 glass powder.

[0082] S2: ZIF-62 glass powder and imidazole (Im) are placed in a reactor, the temperature is raised to 120°C, Im sublimates, and Im vapor reacts with the metal organic framework glass for 3 hours, and the structure is reconstructed to form the MOF-CGC material ZIF-62-Im.

[0083] Example 6

[0084] Preparation of [Zn(HPO4) (H2PO4)2](ImH2)2-Mim

[0085] S1: Place [Zn(HPO4) (H2PO4)2](ImH2)2 crystalline powder in a tubular furnace, and heat it from room temperature to 200°C at a heating rate of 5°C / min under argon protection. After staying at 200°C for 5 minutes, stop heating immediately and cool naturally to room temperature to obtain [Zn(HPO4) (H2PO4)2](ImH2)2 glass powder.

[0086] S2: Place ZIF-62 glass powder and imidazole (Mim) in a reactor, raise the temperature to 120°C, sublimate Mim, and react Mim vapor with the metal organic framework glass for 3 hours to reconstruct the structure to form MOF-CGC material [Zn(HPO4) (H2PO4)2](ImH2)2-Mim powder.

[0087] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a MOF-CGC material, characterized in that: The following steps are involved: S1: Under a protective gas atmosphere, the metal organic framework crystal is heated to a molten state, and then rapidly cooled to obtain the metal organic framework glass; S2: The metal organic framework glass obtained in step S1 and the organic ligand are mixed and placed in a reactor, and heated to induce sublimation of the organic ligand, so that the organic ligand vapor reacts with the metal organic framework glass, and after the reaction is completed, a MOF-CGC material is obtained.

2. The preparation method according to claim 1, characterized in that The metal organic framework crystal is selected from [Zn(HPO4)(H2PO4)2](ImH2)2, [Zn3(H2PO4)6(H2O)3](HbIm), [Zn3(H2PO4)6(H2O)3](HmbIm), [Zn3(H2PO4)6(H2O)3](BTA), [Zn(H2PO4)2(HPO4)](H2dmbIm)2, Zn(HTr)2(H2PO4)2, ZIF-4, Zn(Im)2(GIS), ZIF-62(Zn), ZIF-62(Co), ZIF-76, ZIF-76-mblm, TIF-4, Zn(Im)2 1.95 (bIm) 0.025 (ClbIm) 0.025 、Co 0.2 Zn 0.8 (Im) 1.95 (bIm) 0.025 (ClbIm) 0.025 , any one or more of ZIF-UC-2, ZIF-UC-3, ZIF-UC-4, and ZIF-UC-5.

3. The preparation method according to claim 1, characterized in that: In the step S1, the heating temperature is 50-800°C.

4. The preparation method according to claim 1, characterized in that: In the step S1, the cooling rate is 1-50°C / min.

5. The preparation method according to claim 1, characterized in that: In step S2, the organic ligand is selected from any one or more of imidazole, 2-methylimidazole, 2-aminoimidazole, benzimidazole, 2-chlorobenzimidazole, 5-chlorobenzimidazole, 5-methylbenzimidazole, 5,6-dimethylbenzimidazole, pyridine, p-aminopyridine, 2-aminopyridine, 3-aminopyridine, 1,2,4-triazole, and 1,2,3-triazole.

6. The preparation method according to claim 1, characterized in that: In the step S2, the temperature of the heating treatment is 50-400°C.

7. The preparation method according to claim 1, characterized in that: In step S2, the reaction time is 1 min to 7 d.

8. The preparation method according to claim 1, characterized in that: In the step S1, the components of the protective gas atmosphere are selected from any one or more of nitrogen, helium, and argon.

9. A MOF-CGC material, characterized in that: The MOF-CGC material is prepared by the preparation method described in any one of claims 1 to 8, and the MOF-CGC material includes a metal organic framework crystal phase and a metal organic framework glass phase in any proportion.

10. An application of MOF-CGC material, characterized in that: The MOF-CGC material according to claim 9 is used for gas separation and adsorption.

Citation Information

Patent Citations

  • Methods of synthesizing and recycling metal organic framework systems

    CN116472112A

  • Metal organic framework glass composite material as well as preparation method and application thereof

    CN117718025A